2017
DOI: 10.1161/jaha.117.006757
|View full text |Cite
|
Sign up to set email alerts
|

Visit‐to‐Visit Variability of Fasting Plasma Glucose and the Risk of Cardiovascular Disease and All‐Cause Mortality in the General Population

Abstract: BackgroundThe association of short‐term variability of fasting plasma glucose (FPG) and mortality has been well investigated. However, the relationships between visit‐to‐visit variability of FPG over longer periods of follow‐up and cardiovascular disease (CVD) and all‐cause mortality are unclear. This study aimed to investigate these relationships.Methods and ResultsThe current analysis included 53 607 Chinese participants (mean age, 49.10 years) who were free of CVD in the Kailuan study. Participants were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 34 publications
3
52
0
1
Order By: Relevance
“…However, previous studies examining the prognostic significance of long-term glycemic variability in individuals without diabetes are scarce. In the general population, elevated visit-to-visit FPG variability predicted the risk of CVD and all-cause mortality independent of mean FPG and other baseline variables in 53,607 Chinese participants during a mean follow-up time of 4.9 years (22). Our study demonstrated the consistent association between glycemic variability and the development of type 2 diabetes in both normal and IFG groups after adjusting for confounding factors.…”
Section: Resultssupporting
confidence: 55%
“…However, previous studies examining the prognostic significance of long-term glycemic variability in individuals without diabetes are scarce. In the general population, elevated visit-to-visit FPG variability predicted the risk of CVD and all-cause mortality independent of mean FPG and other baseline variables in 53,607 Chinese participants during a mean follow-up time of 4.9 years (22). Our study demonstrated the consistent association between glycemic variability and the development of type 2 diabetes in both normal and IFG groups after adjusting for confounding factors.…”
Section: Resultssupporting
confidence: 55%
“…To minimize the bias caused by a single measurement of fasting glucose level, we used the mean fasting glucose level measured in both 2009-2010 and 2011-2012. Furthermore, glycemic variability, a strong predictor of CV events [27][28][29][30], could not be assessed because of the limited instance of fasting glucose measurements, in the present study. Third, the controlled fasting glucose levels during the future follow-up period could not be predicted.…”
Section: Discussionmentioning
confidence: 93%
“…79 More recently, GV has also been associated with higher risk of mortality in the general population. 80 Interestingly, increased GV has been found to be strongly associated with mortality in ICU in persons without diabetes, but less so in those with diabetes. 81 Similarly, a poorer 30-day functional outcome following acute intracerebral hemorrhage was observed in those without diabetes and increased GV.…”
Section: Glucose Variability: Hard Outcomes In Persons With and Withomentioning
confidence: 99%